Trap‐induced persistent luminescence in organic light‐emitting diodes - Zishuang Wu; Cunjian Lin; Rujun Yang; Chenhan Zhan; Yajing Wang; Kai‐Ning Tong; Shihai You; Ying Lv; Guodan Wei; Jumpei Ueda; Yixi Zhuang; Rong‐Jun Xie (InfoMat)
Abstract Luminescence in organics that lasts for seconds to a few hours after light excitation has been reported recently, showcasing significant application potentials in flexible electronics and bioimaging. In contrast, long‐lasting luminescence that can be electrically excited, whether in organics or inorganics, is much rarer and often less efficient. In this study, we report persistent luminescence (PersL) in organic light‐emitting diodes (OLEDs) that lasts over 100 s and an energy storage effect beyond 60 min after charging with a direct‐current electric field. Thermoluminescence studies reveal that the PersL in OLEDs is induced by traps formed in a host‐guest molecular system serving as an emission layer (EML) with a trap depth of approximately 0.24 eV, consistent with the results from the same EML materials under light irradiation. Integrating results from electronic spin resonance, and density functional theory calculations, we propose a model delineating the charge carrier migration responsible for the trap‐induced PersL in OLEDs. This study on trap‐induced PersL in OLEDs may deepen our understanding of the luminescence mechanism in organic semiconductors and pave the way for expanding their applications in optoelectronics, energy storage and biological detection technologies.